Strategi Public Relation Dalam Pemasaran Digital: Analisis Kolaborasi Webseries “Pakai Hati Reborn” Dengan Bank BRI Dalam Meningkatkan Literasi Keuangan Masyarakat - Fiwasifi Isyiya; Ida Farida; Rica Anggraini; Siti Muawanah; Siti Nurul Aisyah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
This study examines Bank BRI's Public Relations (PR) strategy in digital marketing through its collaboration with the web series "Pakai Hati Reborn." The goal is to enhance financial literacy among the younger generation. Using qualitative content analysis, this research investigates the communication strategy and its impact on public understanding. The results show that the collaboration successfully increases public interest in financial literacy and strengthens Bank BRI's brand image as a caring financial institution. Digital and entertainment approaches effectively convey educational messages.